Relationship between klotho, neurotrophic factors (BDNF, NGF, GDNF) and cognitive functions in patients with bipolar disorder - Zeynep Çelebi; Esra Yazıcı; Derya Güzel Erdoğan; Onur Davutoglu; Ahmet Bulent Yazıcı (BMC Psychiatry)
Abstract Background Klotho and neurotrophic factors, including brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and glial cell line-derived neurotrophic factor (GDNF), have been shown to play a role in cognitive functions. However, these molecules have not been investigated in bipolar disorder simultaneously to assess the interactions among them and their relationships with cognitive functions. This study investigated the relationships among cognitive function, klotho, and neurotrophic factors in patients with bipolar disorder in the remission period. Methods Male, bipolar disorder (BD) patients (patient group, n = 48) in the remission period and healthy volunteers (control group, n = 48) were included in the study. The Stroop test and Wechsler Memory Scale–Visual Production Subtest were applied, and the serum levels of Klotho, BDNF, GDNF, and NGF were measured with an ELISA reader. Results The klotho protein levels (0.12 ± 0.15 and 0.17 ± 0.16) and NGF levels (34.36 ± 41.99 and 48.54 ± 41.06) in the patient group were significantly lower than those in the control group (Z = -3.071, p = 0.002 and Z = -2.217, p = 0.027, respectively). In the patient group, there was a positive correlation between the klotho and NGF levels (p = 0.003, rs = 0.413), and a negative correlation was detected between the NGF and GDNF levels (p = 0.013, rs = -0.355). Klotho and NGF were predictors of Weshler 40-min test results (adjusted R2 = 0.467), and Klotho and BDNF were predictors of Stroop test colour word reading time (adjusted R2 = 0.391) with other variables. Conclusion In BD patients, klotho, BDNF, GDNF and NGF are associated with cognitive functions and exhibit different characteristics from those of the control group. Nevertheless, the differences related to these molecules seem to be associated with a regulatory system rather than merely an increase or decrease in serum levels.